Perioperative patient outcomes in the African Surgical Outcomes Study: a 7-day prospective observational cohort study. Issue 10130 (21st April 2018) - Biccard, Bruce M; Madiba, Thandinkosi E; Kluyts, Hyla-Louise; Munlemvo, Dolly M; Madzimbamuto, Farai D; Basenero, Apollo; Gordon, Christina S; Youssouf, Coulibaly; Rakotoarison, Sylvia R; Gobin, Veekash; Samateh, Ahmadou L; Sani, Chaibou M; et al.
Summary: Background: There is a need to increase access to surgical treatments in African countries, but perioperative complications represent a major global health-care burden. There are few studies describing surgical outcomes in Africa. Methods: We did a 7-day, international, prospective, observational cohort study of patients aged 18 years and older undergoing any inpatient surgery in 25 countries in Africa (the African Surgical Outcomes Study). We aimed to recruit as many hospitals as possible using a convenience sampling survey, and required data from at least ten hospitals per country (or half the surgical centres if there were fewer than ten hospitals) and data for at least 90% of eligible patients from each site. Each country selected one recruitment week between February and May, 2016. The primary outcome was in-hospital postoperative complications, assessed according to predefined criteria and graded as mild, moderate, or severe. Data were presented as median (IQR), mean (SD), or n (%), and compared using t tests. This study is registered on the South African National Health Research Database (KZ_2015RP7_22) and ClinicalTrials.gov (NCT03044899 ). Findings: We recruited 11 422 patients (median 29 [IQR 10–70]) from 247 hospitals during the national cohort weeks. Hospitals served a median population of 810 000 people (IQR 200 000–2 000 000), with a combined number of specialist surgeons, obstetricians, and anaesthetists totalling 0·7 (0·2–1·9) per 100 000 population. Hospitals did a median of 212 (IQR 65–578) surgical procedures per 100 000 population each year. Patients were younger (mean age 38·5 years [SD 16·1]), with a lower risk profile (American Society of Anesthesiologists median score 1 [IQR 1–2]) than reported in high-income countries. 1253 (11%) patients were infected with HIV, 6504 procedures (57%) were urgent or emergent, and the most common procedure was caesarean delivery (3792 patients, 33%). Postoperative complications occurred in 1977 (18·2%, 95% CI 17·4–18·9]) of 10 885 patients. 239 (2·1%) of 11 193 patients died, 225 (94·1%) after the day of surgery. Infection was the most common complication (1156 [10·2%] of 10 970 patients), of whom 112 (9·7%) died. Interpretation: Despite a low-risk profile and few postoperative complications, patients in Africa were twice as likely to die after surgery when compared with the global average for postoperative deaths. Initiatives to increase access to surgical treatments in Africa therefore should be coupled with improved surveillance for deteriorating physiology in patients who develop postoperative complications, and the resources necessary to achieve this objective. Funding: Medical Research Council of South Africa.